Pengaruh Faktor-Faktor Makro Ekonomi terhadap Return Saham Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2023 - Risyeilla Prizizilia Rosalinsia Koanak; Anthon Simon Y. Kerihi; Siprianus G. Tefa (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to determine the influence of exchange rates, interest rates, inflation, and gross domestic product partially or simultaneously on stock returns. This study uses a quantitative method. The data used is secondary data obtained from the annual financial statements of companies in the food and beverage sub-sector that are listed on the Indonesia Stock Exchange for the 2021-2023 period or through www.idx.co.id and www.yahoo.finance.co.id. The sampling technique used purposive sampling with a sample of 26 food and beverage sub-sector companies that met the criteria for five years of observation. The sample in this study is 11 companies in the food and beverage sub-sector. The results showed that partially the variables of gross domestic product had a positive and significant effect on stock returns, while the variables of exchange rate, interest rates, and inflation did not show a significant influence. However, simultaneously, these four variables have a significant influence on the stock returns of the food and beverage sub-sector for the 2018-2023 period.